The Effect of The Digitalization of Banking Services on Customer Satisfaction at BCA Syariah KCP Kranji - Lisana Aliya; Fitri Yetty; Siwi Nugraheni (Journal of Islamic Economics and Social Science (JIESS), 2021)
A quantitative research that aims to understand the effect of digitizing syariah banking services on customer satisfaction in services that are fast, easy, and can be controlled by customers. The population chosen in this study is people who have or already know the use of mobile banking by distributing questionnaires to 100 respondents. The sampling technique used purposive sampling technique with a Likert scale. This analysis uses IBM SPSS Statistics Version 25.0 software. The results of this study indicate that the Digital Banking System, Service, Easiness, Comfort variable has a positive linear relationship to Customer Satisfaction, namely an increase in Digital Banking System, Service, Easiness, and Comfort will increase Customer Satisfaction as well. Digital Banking System is the only variable that has no significant effect on Customer Satisfaction, while Service, Easiness, Comfort has a significant influence on BCA Syariah Customer Satisfaction due to the rapid development of today's technology that accommodates banking industry services in Indonesia.